Pengembangan Pluralisme Agama di Kalangan Mahasiswa (Analisis atas Proses Pembinaan keagamaan dan Politik Identitas terhadap Religiusitas Mahasiswa di Universitas Bhayangkara Jakarta) - Ahmad Zamakhsari (JURNAL INDO-ISLAMIKA, 2017)
Developing a training in religious pluralism to a young generation at a university level in Indonesia seems to work out as the university is a highly intentional agent of for that coaching. It is a place where its stakeholders, including its students, are inclined to bow to the academic tradition, and where the religious pluralism can be a subject that they study and practice. This process is a potential medium to reduce religious conflict and violence in the country. This paper found this dynamic at the Universitas Bhayangkara Jakarta that perpetuates the religious pluralism by its well-organized academic programs, mainly by its discussions and dialogues. This university applies this training to perpetuate religious tolerance and social harmony among its administrative and teaching staff.